Preparation of three dimensional bimetallic Cu–Ni/NiF electrodes for efficient electrochemical removal of nitrate nitrogen. (May 2022) - Tan, Xiangdong; Wang, Xueqing; Zhou, Tong; Chen, Tianzuo; Liu, Ya; Ma, Chuanjun; Guo, Hongshan; Li, Baozhong
Abstract: It still remains a hotspot and great challenge to efficiently remove the nitrate nitrogen from high salt wastewater. Herein, a novel three dimensional porous bimetallic copper-nickel alloy electrode was fabricated with Ni foam (NiF) as substrate. The physicochemical and electrochemical characterization results showed Cu–Ni/NiF electrode possessed the smaller particle size (0.3–1.0 μm) and electrode film resistance comparing with Ni/NiF and Cu/NiF electrodes. Besides, higher double layer capacitance (Cdl ) for Cu–Ni/NiF electrode indicated more electrochemical active sites could be used in the electrochemical nitrate nitrogen (NO3 − -N) removal. The electrochemical experiments showed the Cu–Ni/NiF electrode had the optimal NO3 − -N reduction ability and almost 100% NO3 − -N removal could be achieved with 30 min. All NO3 − -N removal processes were in accord with the pseudo-first-order reaction kinetics completely. The gaseous nitrogen selectivity for Cu–Ni/NiF electrode could reach 80.9% within 300 min. Stability assessment experiments indicated the Cu–Ni/NiF electrode all kept an excellent stability with Na2 SO4 or NaCl electrolyte and the Cl − addition could significantly improve the gaseous nitrogen selectivity. Finally, a possible removal mechanism of NO3 − -N was proposed. This work offered a direction for designing non-noble bimetallic electrodes for nitrate removal. Graphical abstract: Image 1 Highlights: Three dimensional bimetallic electrodes were fabricated by electro-deposition. Almost 100% NO3 − -N removal could be achieved by Cu–Ni/NiF electrode within 30 min. The NO3 − -N removal processes all followed the pseudo-first-order reaction kinetics. The TN removal for Cu–Ni/NiF electrode could reach 80.9% within 300 min. The Cu–Ni/NiF electrode kept an excellent stability at Na2 SO4 or NaCl electrolyte.